2021
DOI: 10.1149/2162-8777/abddd7
|View full text |Cite
|
Sign up to set email alerts
|

Role of an Al2O3 Passivation Layer during Annealing of 2D-SnS2 Thin Films Grown by Atomic Layer Deposition

Abstract: Tin disulfide (SnS2) is a two-dimensional (2D) post-transition metal chalcogenide (p-TMDC) with considerable potential to compete with other benchmarked 2D-TMDC materials such as MoS2 and WS2. Compared with other 2D-TMDC materials, SnS2 has the strong advantage of being synthesized at low temperature. However, a lower synthetic temperature of SnS2 lessens its thermal stability at high temperature. Thus, many researchers have cautiously handled SnS2 when exposing it to high process temperature. In this paper, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Together, these observations demonstrate that the nanoscale reactors can both retain the melted nanoplates and protect them from environmental reactions. As a related example, it was recently shown that 50 nm-thick Al 2 O 3 encapsulation layers can enable high-temperature annealing of SnS 2 , which resulted in improved crystallinity without material loss or oxidation . The nanoscale reactor design in this study can be used to image such processes at high resolution to gain a mechanistic understanding of transformation processes.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…Together, these observations demonstrate that the nanoscale reactors can both retain the melted nanoplates and protect them from environmental reactions. As a related example, it was recently shown that 50 nm-thick Al 2 O 3 encapsulation layers can enable high-temperature annealing of SnS 2 , which resulted in improved crystallinity without material loss or oxidation . The nanoscale reactor design in this study can be used to image such processes at high resolution to gain a mechanistic understanding of transformation processes.…”
mentioning
confidence: 94%
“…54 Oxide passivation layers have also been shown to increase the allowable annealing temperature during fabrication of LMC devices, resulting in improved crystallinity and electronic properties. 55 Here, we demonstrate the construction of an in situ TEM heating setup featuring an amorphous Al 2 O 3 encapsulation layer that enables investigation of melting, crystallization, and alloying transformations in nanoscale Bi 2 Te 3 platelets without significant material loss or electron beam damage. Melting was observed to progress through the movement of a sharp interface through the Bi 2 Te 3 crystals.…”
mentioning
confidence: 99%
See 2 more Smart Citations